2019
DOI: 10.1016/j.saa.2019.03.111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic characterization of novel GFP chromophore analogues based on aminoimidazolone derivatives

Abstract: In order to improve the fluorescence properties of the green fluorescent protein chromophore, p-HOBDI ((5-(4-hydroxybenzylidene)-2,3-dimethyl-3,5-dihydro-4H-imidazol-4-one), sixteen dihydroimidazolone derivates were synthesized from thiohydantoin and arylaldehydes. The synthesis developed is an efficient, novel, one-pot procedure. The study provides a detailed description of the spectroscopic characteristics of the newly synthesized compounds, using p-HOBDI as a reference. The new compounds all exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In this study, 10 novel compounds ( 1 b – k , listed in Table 1) were designed and synthesised from 2‐thiohydantoin ( 2 ) in two‐step procedures (Figure 2) to enhance the fluorescent activity of the GFP analogue scaffold 1 a . The preceding study revealed the beneficial spectroscopic change of the OH group at position 4 on the benzylidene phenyl ring [31] . Another work showed significant improvement in the Stokes shift when OH was placed to position 2 [3] .…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…In this study, 10 novel compounds ( 1 b – k , listed in Table 1) were designed and synthesised from 2‐thiohydantoin ( 2 ) in two‐step procedures (Figure 2) to enhance the fluorescent activity of the GFP analogue scaffold 1 a . The preceding study revealed the beneficial spectroscopic change of the OH group at position 4 on the benzylidene phenyl ring [31] . Another work showed significant improvement in the Stokes shift when OH was placed to position 2 [3] .…”
Section: Resultsmentioning
confidence: 88%
“…Our recent study revealed that the introduction of a conjugative group (e. g. phenylamino group) to the imidazolone ring enables the fluorescence of the para ‐amino derivatives and it enhances their QY even above that of p ‐HOBDI [31] . The introduction of electron donor substituents into the p ‐HOBDI structure has also been studied to improve the QY, upshift the emission wavelength and increase the Stokes shift.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations